Strategi Belajar Mahasiswa dalam Menyelesaikan Masalah Program Linier dengan Dualitas - Wulandari, Nourma Pramestie; Kurniati, Nani; Salsabila, Nilza Humaira (FKIP Universitas Mataram, 2025)
Duality in linear programming is an essential concept in optimization-based decision making. However, many undergraduate students still struggle to understand and solve duality problems, especially when converting primal to dual models and interpreting their results. This study aimed to explore the learning strategies used by fifth-semester students in solving duality problems. A qualitative case study approach was employed, involving 36 students from a mathematics education program. Data were collected through classroom observations, open-ended tasks, reflective writing, and interviews, and analyzed thematically. The findings revealed that most students (52.8%) used procedural repetition strategies, while others adopted conceptual elaboration (30.6%) and organizational strategies (16.6%). Students who used elaboration and organizational strategies demonstrated deeper conceptual understanding and greater problem-solving flexibility. These results suggest that procedural approaches still dominate, and instructional efforts should focus on fostering more reflective and meaningful learning strategies among students.